Skills demand and suply in the European Union. - Mospan Natalia (Borys Grinchenko Kyiv Metropolitan University, 2017)
The author of the article presents an analysis of the current situation of demand and supply of specialists in the European Union. The basis for the analysis is the reports of the European Commission, which widely cover this issue. It is worth noting that different EU countries feel the problems of supply and demand in different ways. Their conformity is observed only in Germany, where the number of students graduate each year and enter the labor market in search of work coincides with the requirements of employers in terms of the number of specialists. Other EU countries are in demand for specialists in the scientific, engineering and technology sectors and a quantitative shortage of teachers and doctors. The study is devoted to the questions related to factors that affect the matching between the demand and supply of teachers and doctors. Among such factors is the increase in population, health and education costs. The number of school children is the dominant factor in the demand for teachers. Another factor is educational programs that determine the demand for subject teachers. The policies and priorities of the curriculum have a dominant influence in determining the different types of teachers as well. The demand for physicians depends on the health system. The offer of doctors may differ due to differences in the industry, in particular, the accessibility of education and training for doctors, as well as the conditions of medical service. The results of this study can contribute to a deeper understanding of the current state of the regulating process of higher education interaction with the labor market in Ukraine.